Aplicativo móvil regional para el cálculo nutricional de alimento balanceado para aves de corral del fundo Don Jorge en el distrito de San Juan Bautista 2022 - Guerra Mozombite, Patrick Moisés (2023)
The present thesis research work sought to bring mobile application technology closer to the feeding process of laying birds of the Hy-Line Brown breed in the Don Jorge farm in the district of San Juan Bautista, through the development of an algorithm nutritional calculation; as the main process of the mobile application; that allows a maximum use of the nutrients found in the different food supplies of the birds and that also optimizes the costs for the preparation of these foods. As a general research problem, the following question was posed: Could a mobile application effectively calculate the nutritional balance of food for laying birds of the Hy-Line Brown breed of the Fundo Don Jorge in the community of San Juan Bautista in 2022?; and the following study hypothesis was proposed: A regional mobile application effectively calculates the nutritional balance of food for laying birds of the Hy-Line Brown breed of the Fundo Don Jorge In the community of San Juan Bautista in 2022. The research was observational, non-experimental, descriptive and longitudinal, which helped to determine the benefits of the application in the context of the proposed research question. As our study population, the birds of a shed were considered throughout their life cycle in the Fundo Don Jorge in 2022.